KONFLIK INSENTIF DAN MODEL KINERJA DALAM KEBIJAKAN PENGURANGAN FOOD LOSS AND WASTE - Tardi Setiabudi; Wahyu, Wahyu; Tino Supriantino (Bajang Institute, 2025)
The implementation of Food Loss and Waste (FLW) reduction policies in Indonesia faces challenges due to incentive conflicts between the central government and local governments. Differences in objectives, information asymmetry, and weaknesses in oversight mechanisms lead to opportunistic behavior at the implementation level. This research uses a literature review approach with descriptive qualitative content analysis to synthesize literature related to agency theory and the Van Meter & Van Horn implementation model. Secondary data were obtained through purposive sampling from various relevant journals, books, and policy documents. The research findings identified a data gap of 18% between field information and official reports, indicating constraints in information system integration. Additionally, differences in resource capacity, inter-organizational communication mechanisms, and the characteristics of implementing organizations further exacerbate incentive conflicts. The synthesis of the literature shows that the implementation of a performance-based incentive model, which includes indicators of resource availability, communication effectiveness, and organizational structure, can align national goals with regional operational realities. In conclusion, enhancing digital integration, standardizing data reporting, and strengthening inter-agency coordination are strategic steps to optimize the implementation of FLW policies. Research recommendations include the development of an integrated digital platform and the reformulation of incentive models to enhance accountability, transparency, and the effectiveness of FLW management policies.